2016
DOI: 10.1016/j.scitotenv.2015.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Selection of effective macroalgal species and tracing nitrogen sources on the different part of Yantai coast, China indicated by macroalgal δ15N values

Abstract: • Yantai coast was affected by three types of DIN sources.• Macroalgal species suitable or not for DIN source tracing were suggested; • TN and δ 15 N were affected by nutrient concentrations and the metabolic factors.• P instead of N limited the tissue N uptake in low nutrient concentration sites. G R A P H I C A L A B S T R A C Ta b s t r a c t a r t i c l e i n f o To determine the dominant nitrogen sources and select effective macroalgal species for monitoring eutrophication along the Yantai coast, the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
2
8
0
1
Order By: Relevance
“…Morrissey et al 2013, Pastor et al 2014, Baumgartner and Robinson 2016, and primary producers (e.g. MCclelland and Valiela 1998, Cole et al 2004, Wang et al 2016. Together, results of these studies, including ours, support the finding that high δ 15 N values are good indicators of anthropogenic stress in aquatic systems.…”
Section: Discussionsupporting
confidence: 86%
“…Morrissey et al 2013, Pastor et al 2014, Baumgartner and Robinson 2016, and primary producers (e.g. MCclelland and Valiela 1998, Cole et al 2004, Wang et al 2016. Together, results of these studies, including ours, support the finding that high δ 15 N values are good indicators of anthropogenic stress in aquatic systems.…”
Section: Discussionsupporting
confidence: 86%
“…2 ). The overwhelming dominance of fluvial N transport to the Yellow Sea is corroborated by many papers 18 , 67 71 . Moreover, during warmer seasons in the Yellow Sea, vertical stratification is marked, as evident in sigma t and salinity profiles, constraining upwelling of deeper layers so that upward transport of heavy N may not be a dominant mechanism 66 .…”
Section: Resultsmentioning
confidence: 64%
“…Even in the open Yellow Sea, concentrations of dissolved inorganic nitrogen are 10–80 µM near the coast, and 0.7–5.8 µM offshore 7 . Other reports confirm that concentration of coastal dissolved inorganic nitrogen range 7.4–95 µM 18 and 1–15 µM offshore 10 . Such high concentrations of nitrogen must stimulate the onset and maintain the Ulva bloom.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although some previous reports have used nitrogen stable isotope ratios to apportion nutrient pollution sources between inorganic agricultural fertilizer and wastewater (Derse et al, 2007; Wang et al, 2016), other studies have interpreted δ 15 N enrichment in agricultural watersheds as a sign of nitrogen overenrichment (Wasson et al, 2017). Our study found no indication that agricultural watersheds were associated with lighter stable nitrogen isotope signatures, reflecting that of chemical fertilizers (δ 15 N ≈ 0) (Marion et al, 2005).…”
Section: Discussionmentioning
confidence: 99%